5x-6=3x-35

Simple and best practice solution for 5x-6=3x-35 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-6=3x-35 equation:


Simplifying
5x + -6 = 3x + -35

Reorder the terms:
-6 + 5x = 3x + -35

Reorder the terms:
-6 + 5x = -35 + 3x

Solving
-6 + 5x = -35 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-6 + 5x + -3x = -35 + 3x + -3x

Combine like terms: 5x + -3x = 2x
-6 + 2x = -35 + 3x + -3x

Combine like terms: 3x + -3x = 0
-6 + 2x = -35 + 0
-6 + 2x = -35

Add '6' to each side of the equation.
-6 + 6 + 2x = -35 + 6

Combine like terms: -6 + 6 = 0
0 + 2x = -35 + 6
2x = -35 + 6

Combine like terms: -35 + 6 = -29
2x = -29

Divide each side by '2'.
x = -14.5

Simplifying
x = -14.5

See similar equations:

| 62x+37=x-39 | | 7x+4.6=x+8 | | -6000+20x= | | c^2+2c-63= | | 6x-1+4=4-2x | | 3(15x+75)=540 | | 0.40(94)0= | | v^2-14vf+40f^2=0 | | 3x+4.8=19 | | 3x+2(x-1)=6x-9 | | 2(x-2)=2(2-3x) | | 8z-12=9z-17 | | X+384x=2502 | | 11x+3+60=32x | | f(x)=2x^2-6x | | x^2-24x+58=0 | | 4u^2+6u+9=0 | | 65+31x=45-12x | | 3x+4.9=x+6 | | 9x^6+32x^4+60x+27=0 | | 6c-15=-3c+12 | | 11p-3p=16 | | 16x^3-12x^2+20x-15=0 | | 8y-9+y=9(y-3) | | (4k+3)(k+7)=0 | | 16w^2+31w-2=0 | | 6x+7=8-4x | | 7(5x-5)-3=35x-38 | | 7a-17=7a+1 | | 4x^2-1=6x | | 0=3[x-(3-x)]-5(x+1) | | 9x+2=x+13 |

Equations solver categories